The Mediating Roles of Block Chain Technology Practices on Green Supplier Development Process Towards Sustainability Performance: Indonesia Green Industry Level IV - Hutomo, Arry; Haizam Mohd Saudi, Mohd; Masri, Ridzuan; Sentosa, Ilham; Sinaga, Obsatar (International Journal of Engineering and Technology, 2018)
Implementation of block chain technology has many benefits for some green industries, but there are also cautionary to implementation can be sustained continuously. This paper seeks to advance research development related to green supply chain and block chain technology especially regarding green supplier development process. The purpose of this research is the block chain practices can improve and affect sustainability performance on the green supplier development process. Researchers took 48â€™s of green industry level IV in Indonesia use their approach and analyzed hypothesis in statistically. The results of this study stated have significant impact of block chain practices can be variable to improve sustainability performance on the green supplier development process. This framework can be the basis for the suggestion Green Industry Level IV in maintaining sustainability performance in Indonesia.Â Â